Effect of fatigue on cognitive performance in neurology residents of faculty of medicine Universitas Sumatera Utara - Mahendrayana, Eka; Fitri, Fasihah Irfani; Ramber, Aldy S. (International Journal of Research in Medical Sciences, 2021)
Background: Fatigue is a general term used to describe an overall feeling of tiredness. It is one of the most common complaints of people seen in primary health care. Several previous studies have evaluated the effects of fatigue on cognitive function in various clinical and population settings and yielded different results. This study aimed to investigate the effect of fatigue on cognitive performance in neurology residents of Faculty of Medicine of Universitas Sumatera Utara Methods: This was a crosssectional study involving all of the neurology residents of faculty of medicine universitas Sumatera Utara who fulfilled the inclusion criteria. This study was conducted on November until December 2020. Fatigue was assessed using fatigue severity scale and cognitive performance was assessed using Stroop test. The data was analyse using regression linear test Results: Total subject in this study was 42 subjects consisted of 26 female and 16 male with mean age of 32.02±3.45 years. The mean of FSS score was 33.71±7.41 and the mean of Stroop test score was 46.37±9.16 second. Using regression linear test we found fatigue affect cognitive function with p=0.002; R=0.470 and R2=0.221 and after stratification analysis based on sex of the subjects found that fatigue affect cognitive function in female subjects with p=0.013; R=0.482 and R2=0.232. According to age of the subject, fatigue affect cognitive function in subject >30 years old with p=0.001; R=0.635; R2=0.403 Conclusions: There is significant effect of fatigue on cognitive performance. Particularly in women and age >30 years old.